New Isoflavones with Antioxidant Activity Isolated from Cornulaca monacantha. Issue 12 (26th November 2020) - Mhiri, Rania; Koubaa, Imed; Chawech, Rachid; Auberon, Florence; Allouche, Noureddine; Michel, Thomas
Abstract: In the course of phytochemical and chemotaxonomical investigations of Cornulaca monacantha (Amaranthaceae), two new isoflavones, 3‐(2‐hydroxyphenyl)‐5, 7‐dimethoxy‐6‐(methoxymethyl)‐4 H ‐1‐benzopyran‐4‐one (1 ) and 7‐hydroxy‐3‐(4‐hydroxyphenyl)‐5‐methoxy‐6‐(methoxymethyl)‐4 H ‐1‐benzopyran‐4‐one (2 ) were isolated from the fresh aerial parts of C. monacantha among with three known compounds named vanillic acid (3 ), N ‐ cis‐ feruloyltyramine (4 ) and N ‐ trans‐ feruloyltyramine (5 ). Their structures were elucidated by means of spectroscopic methods including one‐ and two‐dimensional NMR and HR‐ESI‐MS techniques. The isolated compounds exhibited interesting antioxidant activity determined by DPPH, ABTS and TAC tests. Abstract :